Odpowiedź :
a) a+b-(a+b-c) = a+b-a-b+c = c
b) -4(x-5)-3(2-3x) = -4x+20-6+9x = 5x+14
c) -6a³-a(2a+3)(4-3a) = -6a³-a(8a-6a²+12-9a) = -6a³-a(-6a²-a+12) = -6a³+6a³+a²-12a = a²-12a
Mam nadzieję, że pomogłam. Liczę na naj
Pozdrawiam ;)
Odpowiedź:
a) a + b – (a + b – c) = a + b - a - b + c = c
b) - 4 (x - 5) – 3 (2 - 3x) = -4x + 20 - 6 + 9x = 5x + 14
c) -6[tex]a^{3}[/tex]– a (2a + 3)(4 – 3a) = -6[tex]a^{3}[/tex] - a (8a - 6[tex]a^{2}[/tex] + 12 - 9a) =
= -6[tex]a^{3}[/tex] - 8[tex]a^{2}[/tex] + 6[tex]a^{3}[/tex] - 12a + 9[tex]a^{2}[/tex] = [tex]a^{2}[/tex] - 12a